CADMIUM, NICKEL, AND LEAD CONCENTRATION OF MUNICIPAL DUMPSITE IN WESTERN SAMAR, PHILIPPINES - Pearl Aphrodite Bobon-Carnice; Mariss Bostrill Varona; Judy-Ann Ligo Amistoso (BIOTROPIA, 2022)
Heavy metal is one of the major problems due to its accumulation from the soil to the food chain, wherein dumpsites are the primary sources of heavy metal pollution. This study aimed to determine the presence of heavy metals in the soil of Santa Rita, Western Samar dumpsite and to quantify them to obtain knowledge on the possible high contamination that may affect the surrounding areas. This study focused on the presence and concentrations of heavy metals Cd, Ni, and Pb. Eighteen (18) soil samples were acquired within the three sampling sites: shoulder slope, main dumpsite, and foot slope. Each sampling site has three sampling points with a depth of 0 - 30 cm and 30 - 60 cm. Analysis showed that all heavy metals are present in the dumpsite, and the concentrations ranged from 0 - 0.1 mg/kg, 0.09 - 3.7 mg/kg, and 0.09 - 3.7 mg/kg for cadmium, lead, and nickel, respectively. In comparing heavy metals within the sampling sites and depths, only cadmium has a significant difference, while Ni and Pb have no significant difference. Compared with WHO standards, all heavy metals tested still fall within the standard limit. Therefore, the dumpsite is still at a safe level. However, residents should take measures to maintain the soil quality since heavy metal contamination in dumpsites is likely to exacerbate